Primary tuberculous mastitis with cold abscess: a case report - Agrawal, Vishnu; Gupta, Saurabh; Gupta, Shikha; Gupta, Richa (International Journal of Research in Medical Sciences, 2017)
Primary tuberculosis of the mammary gland is a rare disorder often mistaken for other benign and malignant lesions of the breast. We report a case of 18 year old female who presented with swelling over right breast for 4 months. Later she developed creamy discharge from the swelling followed by decrease in its size. It proved to be a case of Primary tubercular mastitis with breast cold abscess.